2021
DOI: 10.1111/psyp.13986
|View full text |Cite
|
Sign up to set email alerts
|

Semantic parafoveal processing in natural reading: Insight from fixation‐related potentials & eye movements

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 62 publications
7
29
3
Order By: Relevance
“…As expected, post-hoc comparisons confirmed that the effect was present at posterior ( b = .43, SE = .19, t = 2.3, p < .05) but not at anterior ( b = .28, SE = .19, t = 1.5, p = .129) or central scalp sites ( b = .19, SE = .19, t = 1.01, p = .309). These results confirm previous reports of occipito-temporal N1 preview validity effects in FRPs (Antúnez et al, 2022; Degno et al, 2019a; 2019b; Dimigen et al, 2012; Dimigen & Ehinger, 2021; López-Peréz et al, 2016; Niefind & Dimigen, 2016; Kornrumpf et al, 2016).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, post-hoc comparisons confirmed that the effect was present at posterior ( b = .43, SE = .19, t = 2.3, p < .05) but not at anterior ( b = .28, SE = .19, t = 1.5, p = .129) or central scalp sites ( b = .19, SE = .19, t = 1.01, p = .309). These results confirm previous reports of occipito-temporal N1 preview validity effects in FRPs (Antúnez et al, 2022; Degno et al, 2019a; 2019b; Dimigen et al, 2012; Dimigen & Ehinger, 2021; López-Peréz et al, 2016; Niefind & Dimigen, 2016; Kornrumpf et al, 2016).…”
Section: Resultssupporting
confidence: 92%
“…However, a reduction of the later N400 component by valid previews was reported in RSVP-flanker studies (Li et al, 2015. The effect was also found to be (marginally) significant in at least three FRP studies (Antúnez et al, 2022, Dimigen et al, 2012López-Peréz et al, 2016), but polarity-reversed in another . It is therefore possible that a main effect of preview validity contributed to the pattern of N400 amplitudes observed on the target.…”
Section: Parafoveal Semantic Processing In Reading 31mentioning
confidence: 78%
See 1 more Smart Citation
“…The semantic parafoveal effects reported in previous FRP studies are not consistent. While some studies have found a semantic parafoveal effect (e.g., Antúnez et al, 2021Antúnez et al, , 2022Kretzschmar et al, 2009;López-Peréz et al, 2016), others did not (Dimigen et al, 2012;Simola et al, 2009). Although the current results support the existence of a semantic parafoveal congruency effect, it is worth noting that the RSVP-flankers paradigm and the reading paradigms differ in many aspects (Dimigen et al, 2011;Kornrumpf et al, 2016), such as the presence or absence of self-paced eye movements, the variability in within-word fixation locations, the possibility for dynamic reading behavior (e.g., refixations, regressions, and word skipping) and the presence or absence of transient stimulus onsets (words flashing up on the screen or being always present).…”
Section: Discussionmentioning
confidence: 99%
“…Antúnez et al (2021) reported a preview effect of semantic relatedness by using non‐cognate translations. To our knowledge, only one FRP study has tested for congruency (rather than semantic relatedness or association) effects of parafoveal words during sentence reading by using a boundary technique; specifically, Antúnez et al (2022) reported a preview effect of semantic plausibility in FRPs. Only such semantic congruency effects can inform us how semantic information is used at the global message level and reveal processes of sentence comprehension.…”
Section: Introductionmentioning
confidence: 99%